Dinamika Penyelesaian Konflik Indonesia Dengan Vietnam Terkait Perbatasan Maritim Zona Ekonomi Ekslusif Indonesia - Muhammad Afifi Alfaridzi (Jurnal Hukum dan Sosial Politik, 2024)
Indonesia is an archipelagic country where a significant part of its territory consists of maritime waters. In the context of jurisdiction governed by the 1985 Law on the Ratification of UNCLOS 1982, Northern Natuna, known for having the largest natural gas reserves in the Asia-Pacific, is recognized as part of Indonesia's (ZEE). However, Vietnam's ratification of UNCLOS in 1982 also asserts a similar claim, stating that geographically, Northern Natuna falls within their territory. Within the framework of principles of peace and international security, various efforts are directed at fostering good relations between countries in conflict resolution by providing a way for conflicting parties to resolve their disputes in accordance with international law. In international law, there are two methods of resolution: through peaceful means and through military action. This research indicates that the resolution of conflicts between Indonesia and Vietnam regarding maritime boundaries in the Exclusive Economic Zone can be achieved through various alternatives within the UNCLOS 1982 framework, such as peaceful resolution and mandatory dispute settlement procedures. Each country has the freedom to choose a resolution alternative that aligns with the wishes of both parties, whether through litigation or non-litigation, as stipulated in Article 280 of UNCLOS 1982.